2019
DOI: 10.30596/ijbe.v1i1.3441
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Quality Academics: The Relationship of Passion, Role Model, Workplace Flexibility, and Career Decision-Making Self-Efficacy

Abstract: Quality academics are crucial to enhance universities’ visibility in attracting more international students to pursue their tertiary education. Consequently, this may lead to the nation aspiration of becoming higher education hub in the region. Thus, understanding individuals’ interest towards pursuing academic career may lead to the recruitment of quality academics. A quantitative study was carried out involving 463 third year undergraduate students in selected universities. Passion, role model, and workplace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Having autonomy by taking time off to meet personal or family issues during work time has been greatly appreciated by employees (Vallerand et al, 2003). Dasan (2019) mentioned that employees require this expectation at work so that individuals can consider pursuing their career choices. With the existence of modern technology, the concept of flexibility at work has been highly correlated with work-life integration as it increases retention, job satisfaction, productivity, commitment, and loyalty (Pleck et al, 1980).…”
Section: Workplace Flexibilitymentioning
confidence: 99%
“…Having autonomy by taking time off to meet personal or family issues during work time has been greatly appreciated by employees (Vallerand et al, 2003). Dasan (2019) mentioned that employees require this expectation at work so that individuals can consider pursuing their career choices. With the existence of modern technology, the concept of flexibility at work has been highly correlated with work-life integration as it increases retention, job satisfaction, productivity, commitment, and loyalty (Pleck et al, 1980).…”
Section: Workplace Flexibilitymentioning
confidence: 99%
“…Whilst research has demonstrated many benefits of FWA, few studies have also been observed into the possibility that autonomy may mediate the Impact of FWA on employees' WLB, which encompasses well-being, happiness, and productivity amid a global pandemic emergency (Azizan & Murad, 2020;Subramaniam et al, 2020;Razlan, 2021). It is suggested that academics working in higher educational institutions (or termed HEIs) experience fewer organizational barriers that generally prevent staff from utilizing FWA to the maximum (Dasan, 2019). This workforce may utilize FWA more frequently than others who are compelled to undertake conventional employment due to their academic nature of work.…”
Section: Problem Of Studymentioning
confidence: 99%
“…While researchers evidence that alternative working arrangements can reduce work-related stress, many organisations in developing countries still prefer the conventional style of working specific hours, due to the belief that attendance monitoring is positively related to productivity. In Malaysia, workplace flexibility is one of the contributing factors towards intention to become an academic (Dasan, 2019), where job autonomy is positively linked with work familyenhancement and explains why flexibility in work arrangement is seen as a favourable aspect in academia. One common type of FWA, implemented globally, is Work From Home (WFH).…”
Section: Introductionmentioning
confidence: 99%